COGNITIVE COMPONENT IN THE STRUCTURE OF THE FUTURE EDUCATORS' READINESS TO FORM GOODWILL IN CHILDREN OF JUNIOR PRESCHOOL AGE - Oksana Domaniuk (Vasyl Stefanyk Precarpathian National University, 2018)
Changes in state policy in the field of education have led to an update of the system of professional training of specialists, in particular future educators of pre-school establishments. Among significant adult educators occupy a leading place, on which the development of basic qualities of a growing person, its moral convictions, acquisition of life social experience, skills of interpersonal relationships depends to a large extent.On the basis of the theoretical analysis of scientific works of specialists in the field of preschool education, the structural components of the readiness of future educators of pre-school establishments for the formation of benevolence in children of the senior preschool age are specified in the article: cognitive, person-motivational, activity. They are organically interconnected, mutually interacting and mutually interacting.The author disclose the content of the cognitive component of the phenomenon under investigation, its criterion and indicators are determined. On the basis of the author's questionnaire of students and the projective method of unfinished sentences, a statement is made that the readiness of future educators for the formation of the specified quality in children 5-7 years of cognitive component is presented. The analysis of answers allowed to isolate the unformed, unsteady, average and optimal levels of the phenomenon under study.The results of the experiment necessitate the search for new approaches in the content and methods of student training. Key words: preparation of specialists of preschool education, readiness of future educators for the formation of benevolence of children of the senior preschool age, readiness structure, cognitive component, levels of readiness.